Exploration of High‐Energy‐Density Materials: Computational Insight into Energetic Derivatives Based on 1, 2, 4, 5‐Tetrahydro‐1, 2, 4, 5‐tetrazine. Issue 10 (19th September 2018) - Jin, Xinghui; Zhou, Jianhua; Hu, Bingcheng
Abstract: Density functional theory was employed to investigate ten 1, 2, 4, 5‐tetrahydro‐1, 2, 4, 5‐tetrazine‐based energetic materials. The heats of formation and detonation properties were calculated by isodesmic reactions and Kamlet–Jacobs equations. The thermal stabilities and impact sensitivities were also estimated to give a better understanding of their decomposition mechanism. The results indicate that all of the designed compounds have high positive heats of formation ranging from 525.1 to 1639.1 kJ mol −1, moderate detonation properties (heats of detonation of 536.6 to 2187.6 cal g −1, theoretical densities of 1.48 to 2.32 g cm −3, detonation velocities of 7.02 to 12.18 km s −1, and detonation pressures of 19.8 to 75.1 GPa), and acceptable stabilities (bond dissociation energies of 0.8 to 104.9 kJ mol −1 ). Taking both the detonation properties and the stabilities into consideration, compoundsA4 andB4 were finally selected as promising candidates of high‐energy‐density materials, as their detonation properties and impact sensitivities were superior to those of HMX. Additionally, the frontier molecular orbitals, electronic densities, electrostatic potentials, and thermal dynamic parameters of compoundsA4 andB4 were also investigated. Abstract : Computational insight : A series of 1, 2, 4, 5‐tetrahydro‐1, 2, 4, 5‐tetrazine‐based energetic materials are designed and investigated by DFT. Their heats of formation, detonation properties, thermal stabilities, and impact sensitivities are calculated accurately. Finally, compoundsA4 andB4 are screened as potential candidates of high‐energy‐density materials, and their electronic properties are also simulated to give a better understanding of their physicochemical properties.